Effects of organic manures and mulches on the growth and yield of broccoli (Brassica oleracea var. italica) in Bangladesh - Dristy Rani, Das; Md Habibur, Rahman; Md Mokter, Hossain; Tahamina, Jahan; Rumpa, Sarker; Akhi, Das (Plant Science Today, 2026)
This investigation was carried out at the Horticulture Farm, Department of Horticulture, Bangladesh Agricultural University, Mymensingh, Bangladesh during the period of November 2022 to March 2023. The purpose of the study was to analyse the effects of various combinations of organic manures and mulches on the growth, yield contributing traits and yield of broccoli. The factorial experiment conducted with 4 levels of organic manures viz., O1: Control (no manure applied), O2: 10 t/ha cowdung, O3:5 t/ha vermicompost, O4: 5 t/ha cowdung + 2.5 t/ha vermicompost and 4 types of mulching materials viz., M1: Control (Non-mulch), M2: Black polythene, M3: Water hyacinth, M4: Rice straw. The study was set up following randomized complete block design (RCBD) with 3 replications. Results show that at 60 days after transplanting (DAT), the maximum plant height (61.35 cm), minimum days required to curd initiation (45.93) and yield per hectare (14.21 t) were obtained from O4 (5 t/ha cowdung + 2.5 t/ha vermicompost) treatment and the minimum results found from the control treatment (O1). In case of mulching treatment, M2 (black polythene) mulching treatment produced the maximum plant height (63.21 cm), minimum days required to curd initiation (47.14) and the highest yield per hectare (14.22 t) at 60 DAT. The results obtained from control treatment were the lowest. It was also observed that the combination of M2O4 (black polythene mulch with 5 t/ha cowdung + 2.5 t/ha vermicompost) gave that highest yield (16.03 t/ha) as compared to the control treatment (7.96 t/ha). It is concluded that black polythene mulch along with 5 t/ha cowdung and 2.5 t/ha vermicompost could be an effective technology to get higher yield of broccoli.